A Case Report of Dyschromatosis Symmetrica Hereditaria with Glucose-6-Phosphate Dehydrogenase Deficiency - Wang P; Tang C; Zhao Y; Wang P (Dove Medical Press, 2023)
Panpan Wang,1 Chenyu Tang,1 Yige Zhao,1 Ping Wang2 1Department of Dermatology, Hangzhou Third People's Hospital, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 2Department of Dermatology, Hangzhou Third People's Hospital, Affiliated Hangzhou Dermatology Hospital of Zhejiang University School of Medicine, Hangzhou, People's Republic of ChinaCorrespondence: Ping Wang, Department of Dermatology, Hangzhou Third People's Hospital, Affiliated Hangzhou Dermatology Hospital of Zhejiang University School of Medicine, Westlake Ave 38, Hangzhou, People's Republic of China, Tel +8613588812862, Email dermwang@aliyun.comAbstract: Dyschromatosis symmetrica hereditaria (DSH) is a pigmented genetic skin disorder with an incompletely understood pathogenesis characterized by reticular hyper- and hypopigmented skin patches on the dorsal aspect of the extremities, freckle-like patches on the face, and unaffected palms and feet. There is no effective treatment available. Glucose-6-phosphate dehydrogenase (G6PD) deficiency has not been reported in the literature of DSH. We describe for the first time a case of DSH with G6PD deficiency and a family history of psychosis.Keywords: dyschromatosis symmetrica hereditaria, glucose-6-phosphate dehydrogenase deficiency, psychosis, ADAR1